Gestational dyslipidaemia and adverse birthweight outcomes: a systematic review and meta‐analysis. (21st May 2018) - Wang, J.; Moore, D.; Subramanian, A.; Cheng, K. K.; Toulis, K. A.; Qiu, X.; Saravanan, P.; Price, M. J.; Nirantharakumar, K.
Summary: Background: Low and high birthweight is known to increase the risk of acute and longer‐term adverse outcomes, such as stillbirth, infant mortality, obesity, type 2 diabetes and cardiovascular diseases. Gestational dyslipidaemia is associated with a numbers of adverse birth outcomes, but evidence regarding birthweight is still inconsistent to reliably inform clinical practice and treatment recommendations. Objective: The aim of this study was to explore the relationship between maternal gestational dyslipidaemia and neonatal health outcomes, namely, birthweight, metabolic factors and inflammatory parameters. Methods: We searched systematically Embase, MEDLINE, PubMed, CINAHL Plus and Cochrane Library up to 1 August 2016 (with an updated search in MEDLINE at the end of July 2017) for longitudinal studies that assessed the association of maternal lipid levels during pregnancy with neonatal birthweight, or metabolic and inflammatory parameters up to 3 years old. Results: Data from 46 publications including 31, 402 pregnancies suggest that maternal high triglycerides and low high‐density‐lipoprotein cholesterol levels throughout pregnancy are associated with increased birthweight, higher risk of large for gestational age and macrosomia and lower risk of small‐for‐gestational age. The findings were consistent across the studied populations, but stronger associations were observed in women who were overweight or obese prior to pregnancy. Conclusions: This meta‐analysis suggested that the potential under‐recognized adverse effects of intrauterine exposure to maternal dyslipidaemia may warrant further investigation into the relationship between maternal dyslipidaemia and birthweight in large prospective cohorts or in randomized trials.